Effects of Nurse Case Management Program on Perceived Quality of Palliative Care and Satisfaction of their Caregivers - แซ่ชิต กัลยา; นิลมานัต กิตติกร (Princess of Naradhiwas University Journal, 2018)
This one-group experimental research, with a pre-test and a post-test aims to compare the perceived quality of care and satisfaction of family caregivers who participated in end-of-life case management programme. Purposive sampling was used to select 30 caregiver who 1) were primary caregivers; 2) were aware of the terminal stage and of their patients who received palliative care approach; and 3) were fully conscious. Samples received end-of-life case management programme consisted of 5 steps including 1)identifying and selecting the case; 2) conducting comprehensive assessment and determining health problems; 3) planning for care as health demands; 4) implementing care management; and 5) evaluating outcome. The Palliative Care Outcome Scale and caregiver satisfaction were used to measure quality of care and caregiver satisfaction questionnaire yielded internal consistency reliability value of 0.82 and 0.90 respectively. The data were analysed using descriptive statistics and pair t-test. The results of this study revealed that after participating in the end-of-life case management programme, samples reported significant an improvement of perceived quality of care (t = 5.43, p < .001) and the satisfaction was at high level. It is suggested that palliative care center or unit should apply this case management nursing programme for end-of-life patients and caregivers, in order to and improve the quality of care.